Hybrid Capture 2 human papillomavirus testing of fine needle aspiration cytology of head and neck squamous cell carcinomas. Issue 9 (12th May 2015) - Hakima, Laleh; Adler, Esther; Prystowsky, Michael; Schiff, Bradley; Schlecht, Nicolas; Fox, Amy; Suhrland, Mark; Khader, Samer N.
<x xml:space="preserve">Abstract</x> Background Human papillomavirus (HPV) positive head and neck squamous cell carcinoma (HNSCC) accounts for 25% of HNSCCs and frequently presents with neck lymph node metastases. We investigated utilizing cytology needle rinse material for HPV DNA testing by Hybrid Capture 2 molecular testing (HC2) as an alternative to p16 immunohistochemistry. Methods Twenty‐two cases of HNSCC presenting with neck lymph node metastasis were prospectively identified by assessment of Diff Quik stained cytology smears. An aliquot of the needle rinse material from the lymph node was analyzed for HPV status using standard HC2 protocol. P16 status was determined with immunohistochemistry on the cell block and/or surgically obtained tumor. Results The mean age of patients with p16 negative HNSCC was 7 years older than p16 positive disease (Table 1). Primary tumor subsites were as follows: 17 oropharynx, 1 hypophayrnx, 3 larynx, and 1 oral cavity (Table 2). All ten p16 negative patients had a history of smoking compared with 33% of p16 positive. Only 3 (25%) of p16 positive tumors demonstrated keratinization, whereas 90% of the p16 negative tumors keratinized (Fig. 1). Twelve of 22 HNSCC cases (55%) were p16 positive, of which 7 (58%) tested positive for HPV by HC2. Ten cases (45%) were negative for p16, all of which were negative for HPV by HC2 (Table 3). Conclusion Molecular testing for HPV using HC2 on needle rinse material of FNA of HNSCC is a useful method of determining HPV status in HNSCC. Diagn. Cytopathol. 2015;43:683–687. © 2015 Wiley Periodicals, Inc.